Fatigue and microstructure of ultrafine-grained metals produced by severe plastic deformation - Mughrabi, Hael; Höppel, Heinz Werner; et al. (Scripta Materialia, 2004)
The cyclic deformation and fatigue behaviour of ultrafine-grained metals produced by the severe plastic deformation technique ECAP (equal channel angular pressing) is discussed briefly with respect to cyclic softening, macroscopic shear banding and fatigue lives. Possibilities to enhance the LCF fatigue resistance by annealing are indicated. © 2004 Acta Materialia Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2004.tech.IW.LWAW.fatigu_4
Keywords: Annealing; ECAP; Fatigue damage; Fatigue life; Microstructure; Ultrafine-grained metals